Uji Sitotoksik Ekstrak Etanol, Fraksi Polar, Semi Polar, dan Non Polar Daun Sirsak (Annona muricata L.) Terhadap Sel HeLa - Harlinda, Gestan Puput, Maryati, Ph.D., Apt (2017)
According to the existing data, cancer is the leading cause death in the world. Therefore need to be explorate natural substances for cancer medication. One of potential plant is soursop leaf (Annona muricata L.). Acetogenin substance in soursop leaf has cytotoxic activity. The purpose of this research is to know the cytotoxic effect of etanol extract, polar, semipolar and non polar fraction of soursop leaf to HeLa cell line, and to know the compound in the extract or fraction that most active. In this research the extraction is use maceration method with etanol 96% as solvent. Fractionationis use vacuum liquid chromatography (VLC) method with n-heksan : etil asetat as mobile phase (5:5, 6:4, 6,5:3,5, 7:3, 8:2). The cytotoxic test was conducted by MTT assay with concentration 500, 250, 125, and 62,5 µg/mL. To determine the class of compounds that contained in extracts or fractions of the most active is use Thin Layer Chromatography (TLC). Result showed that ethanol extract had moderate cytotoxic effects on HeLa cell line with IC50 286,283 μg/mL. Substance compounds in etanol extract of soursop leaf are alkaloid, polivenol, flavonoid, and saponin. Keywords: Annona muricata L., HeLa cell line, MTT assay, cytotoxic